Use of current sheet coupled to an analytical tool to analyze by FEM the harmonic content of armature winding ditribution. Issue 6 (30th November 2020) - Marault, Jérôme; Tounzi, Abdelmounaïm; Gillon, Frédéric; Hecquet, Michel
Abstract : Purpose: For a given rotor, the study of the impact of stator MMF from different winding distributions is usually carried out using analytical model under some simplifying hypotheses to limit time computation. To get more accurate results, finite element model is thus more suitable. However, testing different combinations of stator windings with the same rotor can be tedious when considering the stator slots. Indeed, this introduces mesh constraint, reluctance variation of the air gap and possibly taking into account of the connection between stator coils. To avoid this, a current sheet supplied such to represent the stator MMF and spread all around the inner slotless stator surface can be used. In addition, such an approach can be very useful to didactically assess the effect of each winding space harmonic on machine performance separately. The purpose of this paper is to use a current sheet coupled to an external analytical tool in order to easily test different windings or to quantify the effect of a given spatial harmonic of the winding. Design/methodology/approach: In the proposed approach, the current sheet supply is obtained from an analytical tool that allows determining the spatiotemporal stator MMF of any winding considered. Moreover, stator teeth height is not modelled, and only the thickness of the stator yoke is considered along with the same air gap thickness. Results with the proposed approach are compared to the real stator modelling for two different winding configurations. Last, linear and non-linear magnetic material behaviours are investigated to validate the proposed approach in term of magnetic distribution. Findings: For both studied cases, results in term of local and global physical quantities show good agreement between the real stator modelling and the proposed approach. Originality/value: Current sheet is used with finite element model to study the inherent effect of different winding configurations on local and global physical quantities of an AC electrical machine. The proposed approach avoids the constraints in terms of stator slot geometry and electrical circuit definition. This is very useful to quickly test different winding configurations or to isolate a specific winding space harmonic to quantify its effect on the electrical performances. This cannot be performed using classical modelling as all space harmonics are taken into account.